Inquiry Based Learning (IBL) and Project Based Learning (PjBL) Strategies in Encouraging Students' Creative Thinking: Strategi Inquiry Based Learning (IBL) dan Project Based Learning (PjBL) dalam Mendorong Berpikir Kreatif Siswa - Fauziah Nur; Afrahul Fadhila Daulai; Sapri Sapri (Academia Open, 2025)
General Background: The quality of education plays a pivotal role in shaping productive individuals, yet traditional teacher-centered methods still dominate classroom practices. Specific Background: At SMP Swasta Bangun Mulia P. Brandan, instructional approaches in Islamic Education often rely on passive learning, hindering students’ creative thinking development. Knowledge Gap: Previous studies have mostly examined Inquiry Based Learning (IBL) and Project Based Learning (PjBL) in isolation, with limited integration in religious subjects and minimal focus on private junior high school settings. Aims: This study aims to investigate the individual and combined effects of IBL and PjBL strategies on students’ creative thinking abilities in the context of Islamic Cultural History learning. Results: Using a 2x2 factorial experimental design and ANOVA analysis, results show that both IBL and PjBL significantly enhance creative thinking skills, with PjBL showing a slightly higher average performance. A significant interaction effect was also found between teaching strategies and students’ creativity levels. Novelty: This study is among the first to combine IBL and PjBL in Islamic Education at a private school level, highlighting their synergistic potential. Implications: Findings support the integration of student-centered and project-driven approaches in religious education to foster creativity, suggesting practical pedagogical reforms for teachers in similar educational contexts.Highlight : Both Inquiry Based Learning (IBL) and Project Based Learning (PjBL) significantly improve students' creative thinking skills. PjBL shows stronger and more consistent results, especially among students with high creative potential. Combining IBL and PjBL yields synergistic effects and is especially effective in Islamic education contexts. Keywords : Instructional Media, Literacy and Numeracy, Inquiry-Based Learning, Educational Puzzle, Creative Thinking